Chronic periodontitis and pre-term labour in Brazilian pregnant women: an association to be analysed - Silvio A. Santos-Pereira (Blackwell Synergy, 2007)
Aim: To investigate the association between chronic periodontitis (CP) and prematurity in a group of Brazilian pregnant women from the State of Sa˜o Paulo. Materials and Methods: One hundred and twenty-four women were investigated consecutively in a cross-sectional study, between December 2003 and May 2005. Sixty-eight women had pre-term labour (PTL) and 56 had term labour. A periodontal examination was carried out to identify the presence of CP. Statistical analysis used the Fisher’s exact test or w2 for the discrete variables and the Mann–Whitney test for the non-parametric variables. Odds ratio (OR) was calculated with a 95% confidence interval (CI), to evaluate the relation between CP and pre-maturity. Results: Periodontal indicators, such as clinical attachment loss (po0.0001) and bleeding on probing (p50.012), were observed more in the PTL group. The presence of CP increased the risk for PTL (OR: 4.7, 95% CI: 1.9–11.9), pre-term birth (PTB; OR: 4.9, 95% CI: 1.9–12.8) and low birth weight (o2500 g; OR: 4.2, 95% CI: 1.3–13.3). The pregnant women with PTL presented low levels of schooling (p50.029) and the lowest number of pre-natal appointments (p50.0001) when compared with those with term labour. Conclusion: CP is strongly associated with PTL, PTB and low birth weight in a group of Brazilian pregnant women. These data point to the necessity of regularly investigating CP during pregnancy.